Delta-Like Ligand 4-Notch Signaling in Macrophage Activation. Issue 10 (October 2016) - Nakano, Toshiaki; Fukuda, Daiju; Koga, Jun-ichiro; Aikawa, Masanori
Abstract : The Notch signaling pathway regulates the development of various cell types and organs, and also contributes to disease mechanisms in adults. Accumulating evidence suggests its role in cardiovascular and metabolic diseases. Notch signaling components also control the phenotype of immune cells. Delta-like ligand 4 (Dll4) of the Notch pathway promotes proinflammatory activation of macrophages in vitro and in vivo. Dll4 blockade attenuates chronic atherosclerosis, vein graft disease, vascular calcification, insulin resistance, and fatty liver in mice. The Dll4–Notch axis may, thus, participate in the shared mechanisms for cardiometabolic disorders, serving as a potential therapeutic target for ameliorating these global health problems.